A Comprehensive Approach Towards Optimizing the Xenon Plasma Focused Ion Beam Instrument for Semiconductor Failure Analysis Applications. (5th June 2017) - Subramaniam, Srinivas; Huening, Jennifer; Richards, John; Johnson, Kevin
Abstract: The xenon plasma focused ion beam instrument (PFIB), holds significant promise in expanding the applications of focused ion beams in new technology thrust areas. In this paper, we have explored the operational characteristics of a Tescan FERA3 XMH PFIB instrument with the aim of meeting current and future challenges in the semiconductor industry. A two part approach, with the first part aimed at optimizing the ion column and the second optimizing specimen preparation, has been undertaken. Detailed studies characterizing the ion column, optimizing for high-current/high mill rate activities, have been described to support a better understanding of the PFIB. In addition, a novel single-crystal sacrificial mask method has been developed and implemented for use in the PFIB. Using this combined approach, we have achieved high-quality images with minimal artifacts, while retaining the shorter throughput times of the PFIB. Although the work presented in this paper has been performed on a specific instrument, the authors hope that these studies will provide general insight to direct further improvement of PFIB design and applications.